Estimating micronutrient intakes from Household Consumption and Expenditures Surveys (HCES): An example from Bangladesh - Bermudez, Odilia I.; Lividini, Keith; Smitz, Marc-Francois; Fiedler, John L. (SAGE Publications, 2012)
Globally, there is a scarcity of national food consumption data that could help to assess food patterns and nutrient intakes of population groups. Estimates of food consumption patterns and apparent intakes of energy and nutrients could be obtained from national Household Consumption and Expenditures Surveys (HCES).To use the HCES conducted in Bangladesh in 2005 (HIES2005) to estimate apparent intakes of vitamin A, iron, and zinc.Food acquisition data from HIES2005, which surveyed 10,080 households, were transformed into standard measurement units. Intrahousehold food and nutrient distribution was estimated with Adult Male Equivalent (AME) units. Adequacy of intake was assessed by comparing individual nutrient intakes with requirements and was then aggregated by households.The weighted mean energy intake for the population was 2,151 kcal/person/day, with a range among divisions from 1,950 in Barisal to 2,195 in Dhaka division. The apparent intakes of vitamin A and iron were insufficient to satisfy the recommended intakes for more than 80% of the population in Bangladesh, while apparent intakes of zinc, adjusted by bioavailability, satisfied the requirements of approximately 60% of the population.Using the HIES2005, we were able to produce estimates of apparent food consumption and intakes of some key micronutrients for the Bangladeshi population and observed wide differences among divisions. However, the methodological approaches reported here, although feasible and promising, need to be validated with other dietary intake methods.